Tinjauan Fiqih Munakahat terhadap Tradisi Perkawinan Nyuwita Ngawula di Masyarakat Suku Samin, Kecamatan Kradenan, Kabupaten Blora - M Yosi Ramadan; Ahmad Farishin Ikhwan; Muhibban (Al-Mahkamah: Islamic Law Journal, 2024)
This research aims to examine this tradition from the perspective of munakahat jurisprudence. This research uses a qualitative approach with case study methods and field observations. Data was collected through in-depth interviews with traditional leaders, religious leaders and the Samin tribe community. The Nyuwita Ngawula tradition, a traditional wedding tradition of the Samin tribe which is full of meaning and positive values, has an important role in building marital harmony. This tradition provides an opportunity for the prospective husband and wife to get to know and understand each other before getting married, as well as helping the prospective wife's family to assess the seriousness and abilities of the prospective husband. This tradition requires the prospective husband to stay with his prospective wife for 3-7 days. While living at the prospective wife's house, the prospective husband is obliged to help with household chores in order to get an assessment from the prospective in-laws. This nyuwita mgawula tradition has several positive impacts, such as getting to know each other before marriage, and feeling caring and mutual cooperation in a household relationship. The results of the research show that the Nyuwita Ngawula tradition has some conformity with the principles of munakahat fiqh, such as the existence of a marriage guardian, dowry, and marriage vows. However, there are several aspects that need to be addressed. The conclusion of this research is that the Nyuwita Ngawula tradition needs to be adjusted to be more in line with munakahat fiqh. This can be done through educating the Samin tribe community about the harmony and legal requirements for marriage, as well as separating the residence of the prospective bride and groom during the ngawula period.